NOTE: DIFFERENTIAL SENSITIVITY OF THREE SPECIES OF Drosophila TO TWO CYCLIC HYDROCARBONS - Vijayan, V.A.; Krishnamurthy, N.B. (Annals of Tropical Research, 1988)
Sensitivity of three Drosophila species namely D. melanogaster, D. nasuta nasuta and D. sulfuricaster neonasuta to two cyclic hydrocarbons, namely: Dithranol (1, 8, 9-trihydroxy anthracene), and 2,4-dichloro-1-naphthol was studied. Dithranol at 500, 750 and 1000 ppm and 2,4-dichloro-1-naphthol at 100, 150 and 200 ppm were administered to the larvae of the three species. Larval viability and development of all the species tested were significantly affected. Differential sensitivity of the three species in the light of their biomass is discussed.